2015
DOI: 10.1039/c5nr04995d
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of electrospun polyethylene nanofibers

Abstract: We report on the structure-thermal transport property relation of individual polyethylene nanofibers fabricated by electrospinning with different deposition parameters. Measurement results show that the nanofiber thermal conductivity depends on the electric field used in the electrospinning process, with a general trend of higher thermal conductivity for fibers prepared with stronger electric field. Nanofibers produced at a 45 kV electrospinning voltage and a 150 mm needle-collector distance could have a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 46 publications
4
96
0
Order By: Relevance
“…Thermal bridge method is very successful in measuring thermal conductivity of suspended single polymer fibers and films . However, there are limitations.…”
Section: Theoretical and Experimental Approachesmentioning
confidence: 99%
“…Thermal bridge method is very successful in measuring thermal conductivity of suspended single polymer fibers and films . However, there are limitations.…”
Section: Theoretical and Experimental Approachesmentioning
confidence: 99%
“…However, evaluation of the insulation potential in the electrospun nanofiber sheets is a great challenge, due to their sensitivity to pressure, which modifies the porosity and packaging nanofibers in the material. In general, researchers mainly focus on the thermal conductivity measurements along the individual fiber length, showing extremely high thermal conductivity when compared to bulk materials . In our early study, we have also found high anisotropy in the thermal conductivity of the electrospun thin membranes: These materials are highly conductive in the plane direction but with extreme insulation behavior perpendicular to the plane .…”
Section: Resultsmentioning
confidence: 67%
“…In general, researchers mainly focus on the thermal conductivity measurements along the individual fiber length, showing extremely high thermal conductivity when compared to bulk materials. 62 In our early study, we have also found high anisotropy in the thermal conductivity of the electrospun thin membranes: These materials are highly conductive in the plane direction but with extreme insulation behavior perpendicular to the plane. 63 The transient plane source technique, which is a basis of the hot disk method, is one of the most acceptable methods for the measurement of polymer nanofiber-based materials.…”
Section: Heat Transfermentioning
confidence: 89%
“…With water permeated into the polymer backbone, polymer chains in hydrogel could be stretched. In polymer system, stretching is an effective method to enlarge thermal conductive property in polymer system because of the accompanied better chain alignment and less defects [18,31,32]. The thermal conductivity of the drawn nanofibers could be as high as 104 Wm -1 K -1 .…”
Section: Resultsmentioning
confidence: 99%